Higher Education Systems and International Student Mobility in East Africa: A Colonial Relic Shaped by Neoliberal Imperatives of Internationalization - Amutuhaire, Tibelius (International Journal of African Higher Education, 2025)
The internationalization of higher education (IHE) — especially through international student mobility (ISM) — has been widely studied, but most of this scholarship draws on evidence and perspectives from the global North. As a result, research on IHE often overlooks the specifc historical, political, and socioeconomic contexts that shape student mobility within Africa. This paper employs a mixed-methods approach to investigate how students’ perceptions of the quality, governance, and reputation of HE systems in both their home and host countries inﬂuence patterns of intra-Africa student mobility, drawing on evidence from East Africa. The fndings suggest that the movement of students within the region is shaped not only by practical considerations, but also by colonial legacies, each country’s history of hosting international students, and the impact of neoliberal reforms in HE. By situating student mobility within these broader structural and historical contexts, this study contributes to a more nuanced understanding of how HE systems shape mobility within Africa and adds to the growing body of critical scholarship on internationalization. Ultimately, this work points to the need for more regionally grounded research on student mobility across the global South.